Japanese Government Efforts in Flood Disaster Risk Reduction - Larissa Jusivani; IDK Kerta Widana; Fauzi Bahar; Pujo Widodo; Herlina Juni Risma Saragih; Kusuma, Kusuma (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Japan is an island nation prone to floods and tsunamis. The mountains that dominate Japan form short rivers with steep slopes. The rivers transport sediment to the plains, creating medium-sized floodplains. Japan's rivers are prone to flash floods due to their steep basin slopes and relatively short lengths. The ratio of peak discharge to watershed area is relatively large, ranging from 10 to 100 times that of major rivers in other countries. The water level rises and falls very quickly. This research aims to find out the Japanese Government's Efforts in Flood Disaster Risk Reduction. The method used in this research is descriptive qualitative research using purposive sampling technique on the activities of the Overseas Work Lecture (KKLN). Informants appointed as samples are Dr. Aulia Fabianda Anwar Tinumbang from Asisstant Professor. Graduate School of Engineering Kyoto University. KKLN activities are organized by the Defense University Disaster Management Study Program online through the Zoom application. KKDN activities were attended by all 26 Disaster Management Study Program students and also attended by the Head of the Disaster Management Study Program and Disaster Management study program staff. The results showed that the Japanese Government's efforts to reduce flood disaster risk and increase national security.